The Effect of Digitalization and the Work Environment on Employee Performance at STPN Yogyakarta - Megananta Renatabumi; Fereshti Nurdiana Dihan (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the influence of digitalization and work environment on employee performance at the National Land College (STPN) Yogyakarta. A quantitative associative research approach was employed, involving 47 employees as respondents. Data were collected through questionnaires, observation, and documentation and analyzed using multiple linear regression, t-test, F-test, Pearson correlation, and coefficient of determination (R²). The results show that digitalization has a significant positive effect on employee performance, with a t-count of 2.940 > t-table 1.680 and a significance value of 0.005 < 0.05. The work environment also has a significant positive effect, with a t-count of 3.980 > 1.680 and a significance value of 0.000 < 0.05. Simultaneously, digitalization and work environment significantly influence employee performance, with an F-count of 49.275 > 3.204 and a significance value of 0.000 < 0.05. The coefficient of determination indicates that both variables explain 69.1% of employee performance, while 30.9% is influenced by other factors. Pearson correlation results indicate strong relationships between digitalization and performance (r = 0.762) and work environment and performance (r = 0.794). These findings highlight the importance of digitalization and a conducive work environment in improving employee performance.